Prilagoditve in pripomočki pri rekreaciji in športu invalidov - Čander, Jana (Rehabilitacija (Ljubljana), 2019)
Recreation and sport are essential in every individual's life. The article relates to individual adjustments with or without special equipment for recreation and sports for the disabled. It highilghts the options and opportunities for activities. The article confirms the statement of Mr Peter Eriksson, former successful Canadian head coach for para athletics: "Don't look for the limitations; look for the possibilities."
Keywords: adopted equipment; disabled persons; invalidi; osebe z zmanjšanimi zmožnostmi; prilagojeni pripomočki; recreation; rekreacija; sports; Sports for Persons with Disabilities; sports wheelchairs; športi; športni vozički